Effect of exercise-induced body fluid redistribution on body composition in males using dual energy X-ray absorptiometry - Carpio Rivera, Elizabeth (2024)
We studied the effect of exercise-induced body fluid redistribution on dual-energy x-ray absorptiometry (DXA) body composition scores. Thirty males completed 30-min of upper-body exercise (UBE), lower-body exercise, and seated non-exercise control (NEC). ANOVA determined interactions between experimental conditions and measurements on body composition variables. For UBE, mean pre to post differences were found on tissue fat (M = 0.35 ± 0.12%; CI95%diff = 0.10 to 0.59%; p = 0.007), region fat (M = 0.32 ± 0.11%; CI95%diff = 0.09 to 0.55%; p = 0.008), lean mass (M = 0.27 ± 0.01 kg; CI95%diff = 0.18 to 0.37 kg; p ≤ 0.0001), and total mass (M = 0.27 ± 0.05 kg; CI95%diff = 0.17 to 0.36 kg; p ≤ 0.0001). Mean tissue pre to post differences were found for the total body in the NEC (M = 0.10 ± 0.04 kg; CI95%diff = 0.03 to 0.18 kg; p = 0.008), UBE (M = 0.19 ± 0.03 kg; CI95%diff = 0.14 to 0.24 kg; p ≤ 0.0001), and LBE (M = 0.31 ± 0.04 kg; CI95%diff = 0.24 to 0.39 kg; p ≤ 0.0001) conditions. High absolute reliability was found within experimental conditions. These findings have practical implications for technicians, since acute exercise elicited small changes in body composition scores using DXA.